A dry electrode comprising a mixure powder for an electrode
The dry electrode manufacturing method improves conductive material dispersibility through heat-pressing and evaluation, addressing resistance issues and enhancing battery performance.
Patent Information
- Application Number
- KR1020240037976
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-04-20
- Filing Date
- 2024-03-19
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-04-20
AI Technical Summary
Existing dry electrode manufacturing methods face challenges in achieving high dispersibility of conductive materials due to shear forces during production, leading to fractured conductive paths and increased resistance, which degrades battery performance.
A dry electrode manufacturing method involving heat-pressing a mixed powder of electrode active material and binder polymer to form a sheet with specific conductivity dispersion indices, along with a method to evaluate dispersibility using scanning diffusion resistance microscopy.
The method enhances conductive material dispersibility, reducing internal and interfacial resistance, improving battery efficiency and lifespan by maintaining consistent conductive paths and enabling quantitative evaluation of dispersibility.
Smart Images

Figure 112024030873988-PAT00006_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a dry electrode comprising a mixed powder for manufacturing a dry electrode and having a high dispersion of conductive material. Background Technology
[0002] As interest in energy storage technology continues to grow, research and development in electrochemical devices are steadily increasing as application fields expand to include mobile phones, tablets, laptops, camcorders, and even electric vehicles (EVs) and hybrid electric vehicles (HEVs). Electrochemical devices are receiving the most attention in this regard, and among them, the development of rechargeable lithium-ion batteries is a focal point of interest. Recently, research and development in this area has led to the design of new electrodes and batteries to improve capacity density and specific energy.
[0003] Recently, a dry-type electrode manufacturing method that does not involve the use of solvents has been proposed to reduce the degradation of electrode materials caused by solvents used during electrode manufacturing or side reactions caused by residual organic solvents after manufacturing.
[0004] A dry electrode can be manufactured by mixing electrode materials, such as an electrode active material, a conductive material, and a binder resin, in a powder state without using a solvent to produce a mixed powder for the electrode, calendering the mixture to produce a free-standing type dry electrode film, and laminating the film with a current collector. For example, referring to prior art such as U.S. Patent Published US2005-0266298A1, a method has been proposed in which the binder is fiberized through a high-shear mixing process, such as jet-milling, during the manufacture of an electrode composite, and then the mixture is compression-molded into a film form.
[0005] When manufacturing electrodes, methods to increase the content of active material in the electrode are being considered to improve energy density; however, in this case, the content of conductive material decreases relatively, which may increase resistance and degrade the output characteristics of the battery. For electrodes manufactured by conventional wet processes, methods were applied to maximize the content of the electrode active material by increasing dispersibility even when using a relatively small amount of conductive material, such as using linear conductive material or adding a dispersant during slurry preparation.
[0006] However, when manufacturing electrodes dry without using solvents, it is difficult to achieve improved dispersibility through the introduction of dispersants. Furthermore, since strong shear forces are applied during the preparation of mixed powders for electrodes, there is a problem where the conductive material fractures due to the shear force even when linear conductive material is introduced, failing to maintain its original length and thus failing to properly form a conductive path. Accordingly, research is required on dry electrode manufacturing methods that can improve the dispersibility of conductive materials during dry electrode production. Additionally, there is a need to develop an evaluation tool capable of verifying the dispersibility of conductive materials in dry electrodes. The problem to be solved
[0007] The present invention aims to provide a dry electrode with high dispersion of conductive material. Another objective is to provide a method for verifying the degree of dispersion of conductive material in a dry electrode. It will be readily apparent that other objectives and advantages of the present invention can be realized by the means or methods described in the claims and combinations thereof. means of solving the problem
[0008] The first aspect of the present invention is a dry electrode for an electrochemical device, wherein the dry electrode comprises an electrode active material layer derived from a dry electrode film, and the dry electrode active material layer comprises a mixed powder for electrodes, wherein the mixed powder for electrodes is heat-pressed to form a sheet shape having a predetermined thickness, and wherein the mixed powder for electrodes comprises an electrode active material and a binder polymer.
[0009] The above electrode active material layer has a conductivity dispersion index 1 (Index 1) according to [Equation 1] below for one or more arbitrary cross-sections inside, which is 3.5 μm -1 The above and / or the conductivity dispersion index 2 (Index 2) according to [Equation 2] below is 10 or more.
[0010] [Equation 1]
[0011] Index 1(㎛ -1 ) = Boundary measured / A
[0012] [Equation 2]
[0013] Index 2 = Boundary m easured / L circle
[0014] In the above [Equation 1] Boundary measured represents the perimeter of the conductive material region measured at a predetermined cross-section of the electrode active material layer, and A represents the area of the portion defined as the conductive material region measured at a predetermined surface of the electrode active material layer, and in the above [Equation 2] L circle is the circumference of a circle having an area equal to the area of the measured conductive material region.
[0015] A second aspect of the present invention is, in the first aspect, wherein the electrode active material layer has a conductivity dispersion index 1 (Index 1) according to [Equation 1] for one or more arbitrary cross-sections inside, of 3.5 μm -1 This is the case, and the conductivity dispersion index 2 (Index 2) according to [Equation 2] is 10 or greater.
[0016] A third aspect of the present invention is that, in the first or second aspect, the dispersion index 1 and dispersion index 2 are
[0017] (Step 1) A step of obtaining a cross-sectional sample in which an arbitrary cross-section inside the electrode active material layer is exposed;
[0018] (Step 2) A step to obtain a 2D scale map of the resistance distribution of the sample cross-section;
[0019] (Step 3) a step of masking a conductive material region; and (Step 4) a step of calculating the perimeter and area of the masked region, substituting them into Equation 1 and / or Equation 2, and confirming the dispersion of the conductive material in the electrode active material layer; are calculated by a method for evaluating the dispersion of the conductive material.
[0020] A fourth aspect of the present invention is that, in any one of the first to third aspects, the electrode active material layer is formed on one side of the electrode current collector, and the cross-section(s) are a plane parallel or perpendicular to the surface of the electrode active material layer facing the current collector.
[0021] A fifth aspect of the present invention is that, in any one of the first to fourth aspects, the binder polymer is fiberized, and the fiberization is the result of being performed by a method of kneading by shear stress.
[0022] A sixth aspect of the present invention is that, in any one of the first to fifth aspects, the binder polymer comprises polytetrafluoroethylene (PTFE), polyolefin, or a mixture thereof.
[0023] A seventh aspect of the present invention is a method for manufacturing a dry electrode according to any one of the first to fifth aspects, the method comprising the steps of mixing an electrode material including an electrode active material and a binder polymer (S10), kneading the mixed electrode material (S20), grinding the result of step (S20) to obtain an electrode composite powder (S30), and press-molding the electrode composite powder to manufacture a freestanding type dry electrode film (S40), wherein step (S20) is performed in a temperature range of 60°C or higher.
[0024] The eighth aspect of the present invention is that, in the seventh aspect, the (S20) is performed in a temperature range of 60°C to 250°C.
[0025] A ninth aspect of the present invention comprises, in the seventh or eighth aspect, a step of laminating the dry electrode film and the current collector by a lamination process.
[0026] The tenth aspect of the present invention relates to an electrochemical device, wherein the electrochemical device comprises an anode; a cathode; and a separator or solid electrolyte membrane interposed between the anode and the cathode, and at least one of the anode and the cathode is a dry electrode according to the first to sixth aspects. Effects of the invention
[0027] The dry electrode obtained by the manufacturing method according to the present invention exhibits high dispersibility of the conductive material within the electrode active material layer. Accordingly, when the content of the conductive material within the electrode is constant, higher dispersibility has the effect of reducing the internal resistance of the electrode active material layer and the interfacial resistance with the current collector. Furthermore, when a dry electrode with high dispersibility is applied to a battery, the Ohmic resistance is reduced during battery operation, thereby improving voltage drop and enhancing high-output efficiency. If the dispersibility of the conductive material is extremely poor, variations in the degradation of the electrode active material may occur depending on the location within the electrode, which is disadvantageous to battery life characteristics. Additionally, the evaluation tool according to the present invention can verify the dispersibility of the conductive material within the electrode as a quantitative value. Brief explanation of the drawing
[0028] The drawings attached to this specification illustrate preferred embodiments of the present invention and serve to help to better understand the technical concept of the present invention together with the description of the invention above; therefore, the present invention is not to be interpreted as being limited only to the matters described in such drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings included in this specification may be exaggerated to emphasize a clearer explanation. Figure 1 is an image of the SSRM of Example 1, and Figure 2 is an image confirmed by masking the conductive material area. Figure 3 is an image of the SSRM of Comparative Example 1, and Figure 4 is an image confirmed by masking the conductive material area. Figure 5 shows the histogram of Example 1, and Figure 6 shows the histogram of Comparative Example 1. FIG. 7 is a schematic diagram of an electrode according to one embodiment of the present invention. Figure 8 is a schematic diagram for calculating the QBR value of the silver electrode active material layer. FIG. 9 is a schematic diagram of a process for manufacturing a unit film for an electrode according to one embodiment of the present invention. FIG. 10 is a schematic diagram of an electrode lamination process according to one embodiment of the present invention. Figures 11a and 11b schematically illustrate a method for preparing an electrode cross-section sample. FIG. 12a is a histogram of Example 7, and FIG. 12b shows the overlapping shape of the active material region and the conductive material region. Figure 13 is an image of the SSRM of Example 5 and an image confirmed by masking the conductive material area. Figure 14 is an image of the SSRM of Example 6 and an image confirmed by masking the conductive material area. Figure 15 shows an SSRM image of the electrode of Example 7, and Figure 16 is an image confirmed by masking the conductive material region thereof. FIG. 17 is a result image of the electrode of Example 7 in which the conductive material region is masked without correction in the obtained histogram, and FIG. 18 is a result image of the electrode of Example 7 in which the conductive material region is masked after correction. Figure 19 shows a display screen showing the area and perimeter of the conductive material region calculated using Gwyddion software. Specific details for implementing the invention
[0029] Hereinafter, the present invention will be described in more detail to aid in understanding the invention.
[0030] Terms and words used in this specification and claims shall not be interpreted as being limited to their ordinary or dictionary meanings, but shall be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.
[0031] The terms used in this specification are used merely to describe exemplary embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise.
[0032] Furthermore, throughout the specification, when a part is described as "including" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0033] Additionally, terms such as “about,” “substantially,” as used throughout this specification, are used to mean at or near the stated value when inherent manufacturing and material tolerances are presented in the stated meaning, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosure in which precise or absolute values are mentioned to aid in understanding this invention.
[0034] Throughout this specification, the description “A and / or B” means “A or B or both.”
[0035] The present invention relates to a dry electrode manufactured by pressurizing a mixed powder for a dry electrode. It also relates to a method for manufacturing the dry electrode. In the present invention, the dry electrode can be used as an electrode for an electrochemical device such as a lithium-ion secondary battery.
[0036] dry electrode
[0037] The dry electrode is explained in more detail below.
[0038] In the present invention, the dry electrode comprises an electrode active material layer derived from a self-supporting dry electrode film. For example, the dry electrode may comprise a current collector and an electrode active material layer derived from a dry electrode film disposed on at least one side of the current collector, and the dry electrode film and the current collector may be formed by bonding through a lamination process or the like.
[0039] dry electrode film
[0040] The above dry electrode film refers to a film manufactured in the form of a single sheet of a free-standing type using an electrode material comprising an electrode active material and a binder, without the involvement of a solvent. In this specification, the term "free-standing type" means that it can maintain a shape independently without relying on other components and can be moved or handled on its own. In the present invention, the dry electrode film may be formed by compressing a mixed powder for electrodes, as described below. For example, the mixed powder may have a shape forming a layered structure by being accumulated through compression. The mixed powder is a powdered electrode material comprising an electrode active material and a binder polymer, and may be obtained by crushing a mass of a mixture containing an electrode active material and a binder polymer, for example, as described below.
[0041] Content of ingredients
[0042] Meanwhile, in one embodiment of the present invention, the electrode active material layer may contain 80 wt% or more or 90 wt% or more of the electrode active material relative to the total weight of the electrode active material layer. In addition, in one embodiment of the present invention, the electrode active material layer may further include a conductive material as needed. The conductive material may be included in an amount of 20 wt% or less, 10 wt% or less, or 5 wt% or less relative to 100 wt% of the electrode active material layer, and may be included in an amount of 0.1 wt% or more when considering conductivity. For example, the conductive material in the electrode active material layer may be included in a range of about 0.1 to 5 wt%.
[0043] According to one embodiment of the present invention, the content of the electrode active material in the electrode active material layer may be 85 wt% to 98 wt%. Within the above range, the content of the binder polymer may be 0.5 to 10 wt%, and the content of the conductive material may be 0.5 wt% to 5 wt%.
[0044] Meanwhile, in the present invention, the electrode active material layer is derived from a dry electrode film, and the content ratio of the materials in the dry electrode film may be included in the same range as the electrode active material layer.
[0045] Electrode active material
[0046] Meanwhile, the electrode active material layer may include a positive electrode active material or a negative electrode active material depending on the polarity of the battery. Non-limiting examples of the positive electrode active material include lithium transition metal oxides or lithium metal iron phosphate, and are not limited to metal oxide forms, such as, for example, layered compounds such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2), or compounds substituted with one or more transition metals; chemical formula Li 1+x Mn 2-x Lithium manganese oxides such as O4 (where x is 0 to 0.33), LiMnO3, LiMn2O3, LiMnO2, etc.; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, Cu2V2O7, etc.; chemical formula LiNi 1-x M x Ni-site type lithium nickel oxide represented by O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B, or Ga, and x = 0.01 ~ 0.3); chemical formula LiMn 2-x M x Lithium manganese composite oxides represented by O2 (where M = Co, Ni, Fe, Cr, Zn, or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li in the chemical formula is substituted with alkaline earth metal ions; lithium metal phosphate LiM P Examples include O4 (where M is M = Fe, CO, Ni, or Mn), disulfide compounds; Fe2(MoO4)3, but are not limited to these.
[0047] Non-limiting examples of the above-mentioned cathode active material include carbon such as non-graphitized carbon, graphite-based carbon; LixFe2O3(0 <x ≤1), Li x WO2(0≤x≤1), Sn x Me 1-x Me y O z Metal composite oxides such as (Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, Group 1, Group 2, and Group 3 elements of the periodic table, halogens; 0x≤1; 1≤y≤3; 1≤z≤8); lithium metal; lithium alloy; silicon alloy; tin alloy; silicon oxides such as SiO, SiO / C, SiO2; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni based materials, etc. may be used.
[0048] Binder polymer
[0049] In the present invention, the binder polymer is not limited to any specific type as long as it is capable of fibrillation in the manufacturing method described below, particularly in the process of manufacturing the mixture mass. Fibrillation refers to a treatment in which the polymer is divided into fine fibers, and can be performed, for example, using mechanical shear force. The surface of the polymer fiber thus fibrillated is loosened to generate a large number of fine fibers (fibrils). Non-limiting examples of such binder polymers may include polytetrafluoroethylene (PTFE), polyolefin, or mixtures thereof, and specifically, may include polytetrafluoroethylene (PTFE), and more specifically, may be polytetrafluoroethylene (PTFE). Specifically, the polytetrafluoroethylene (PTFE) may be included in an amount of 60% by weight or more based on the total weight of the binder polymer. Meanwhile, at this time, the binder material may additionally include one or more of PEO (polyethylene oxide), PVdF (polyvinylidene fluoride), PVdF-HFP (polyvinylidene fluoride-cohexafluoropropylene), and polyolefin-based polymers.
[0050] Challenge
[0051] In the present invention, the electrode active material layer of the dry electrode may further include a conductive material. In a specific embodiment of the present invention, the conductive material may be included in the electrode mixed powder and introduced into the electrode active material layer. The conductive material is not particularly limited as long as it has conductivity without causing chemical changes in the battery, and for example, graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermal black; conductive fibers such as carbon fiber or metal fiber; metal powders such as carbon fluoride, aluminum, or nickel powder; conductive whiskey such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive materials such as polyphenylene derivatives may be used. However, in detail, to ensure uniform mixing of the conductive material and to improve conductivity, it may include one or more selected from the group consisting of activated carbon, graphite, carbon black, and carbon nanotubes, and more specifically, it may include activated carbon. Meanwhile, in one embodiment of the present invention, it is desirable to increase the amount of carbon black-type dot-shaped conductive material used in the process of manufacturing a mixed powder for electrodes for dry electrode manufacturing in order to improve dispersibility.
[0052] Filler
[0053] Meanwhile, in some cases, a filler that inhibits the expansion of the electrode may be additionally added to the above mixture. The filler is not particularly limited as long as it is a fibrous material that does not cause chemical changes in the battery, and for example, olivine-based polymers such as polyethylene and polypropylene; or fibrous materials such as glass fibers and carbon fibers are used.
[0054] The whole house
[0055] Meanwhile, in one embodiment of the present invention, the current collector is not particularly limited as long as it has high conductivity without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, copper, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. The current collector may also form fine irregularities on its surface to increase the adhesion of the positive active material, and various forms such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics are possible.
[0056] Meanwhile, in one embodiment of the present invention, the current collector may be used having a conductive primer coated wholly or partially on its surface to lower resistance and improve adhesion. Here, the conductive primer may comprise a conductive material and a binder, and the conductive material is not limited to any material that exhibits conductivity, but may be, for example, a carbon-based material. The binder may include fluorine-based (including PVDF and PVDF copolymers), acrylic binders, and water-based binders that are soluble in solvents.
[0057] Dispersion of challenge material
[0058] In the present invention, the electrode active material layer has a conductivity dispersion index 1 (Index 1) according to [Equation 1] below for one or more arbitrary cross-sections inside, which is 3.5 μm -1 The above and / or the conductivity material dispersion index 2 according to [Equation 2] below is 10 or higher. Preferably, the electrode active material layer has a dispersion index 1 of 3.5 μm. -1 The above is as follows, and the dispersion index 2 is 10 or greater. Meanwhile, the electrode active material layer has an index 1 of 40㎛. -1It is preferable that it be less than or equal to. In addition, it is preferable that the index 2 of the electrode active material layer is 50 or less. The dispersion index 1 and dispersion index 2 are the perimeter of the portion defined as the conductive material region from the result (2D mapping image) obtained by visualizing one or more arbitrary cross-sections inside the electrode active material layer on a two-dimensional scale ( Boundary measured ) and area( A After deriving ), the above values can be calculated by substituting them into Equation 1 and Equation 2 below.
[0059] [Equation 1]
[0060] Index 1(a -1 ) = Boundary measured / A
[0061] In the above [Equation 1] Boundary measured represents the perimeter of the portion defined as the conductive material region, measured at a predetermined cross-section of the electrode active material layer, and A represents the area of the portion defined as the conductive material region, measured at a predetermined cross-section of the electrode active material layer. In Equation 1 above, a is the unit used. If the unit of perimeter is μm, the unit of exponent 1 is μm. -1 This can be.
[0062] [Equation 2]
[0063] Index 2 = Boundary measured / L circle
[0064] In [Equation 2] above Boundary measured is equal to Equation 1, and L circle is the circumference of a circle having an area equal to the area of the conductive material region defined above. For any closed curve, the case where the circumference is smallest is when the shape of the closed curve is a circle. Accordingly, the total area of the conductive material region ( AA virtual circle having the same area as ) is assumed, and the circumference of the circle is calculated. The larger the value of Index 2, which is obtained by dividing the circumference of the actual conductive material area by the circumference of the virtual circle, the higher the dispersion.
[0065] The above L circle It can be calculated based on the following formulas 1 and 2.
[0066] [Formula 1]
[0067]
[0068] [Equation 2]
[0069]
[0070] Therefore, the above Equation 2 can be expressed as Equation 2A below.
[0071] [Equation 2A]
[0072]
[0073] In other words, the area of a circle is {(radius of the circle(r)) 2 Since it is calculated as {× π}, the radius (r) of the virtual circle can be determined from this, and once the radius is determined, the circumference (circumference, 2π) of the virtual circle can be calculated.
[0074] The higher the values of the above dispersion indices 1 and 2, the more the conductive material is not aggregated or locally distributed, but is uniformly dispersed within the electrode active material layer. That is, having a high value for the circumference of the conductive material region relative to the area of the conductive material region, or having a high value for the circumference of the conductive material region relative to the circumference of a circle having the same area as the conductive material region, means that the conductive material is uniformly distributed within the electrode.
[0075] For example, the indices 1 and 2 can be identified for two or more different cross-sections of the electrode active material layer, and the index 1 for all cross-sections is 3.5㎛-1 This is the case, and the exponent 2 for all cross-sections is 10 or greater.
[0076] In the present invention, the cross-section(s) may be formed parallel to the surface facing the current collector. Alternatively, the cross-section(s) may be formed in a direction parallel to the surface facing the current collector, in a direction perpendicular to the surface facing the current collector, or formed at a predetermined angle to the surface facing the current collector. Since the present invention is intended to verify the degree of dispersion of the conductive material within the electrode active material layer, the angle between the exposed surface and the surface facing the current collector is not limited to a specific range as long as the interior is exposed to the extent that the indices 1 and 2 can be verified.
[0077] In one embodiment of the present invention, Index 1 identified in a cross-section of a predetermined portion within a range of up to 10% thickness in the thickness direction from top to bottom of the electrode active material layer, and Index 1 identified in a cross-section of a predetermined portion within a range of up to 10% thickness in the thickness direction from bottom to top, are 3.5 μm -1 It may be greater than or equal to. In addition, Index 2 confirmed in a cross-section of a predetermined portion within a range of up to 10% thickness in the thickness direction from top to bottom of the electrode active material layer, and Index 2 confirmed in a cross-section of a predetermined portion within a range of up to 10% thickness in the thickness direction from bottom to top, may be 10 or greater.
[0078] Meanwhile, the lower part of the electrode active material layer refers to a surface facing the current collector (current collector facing portion), and the upper part may be a surface on the opposite side of the current collector facing portion (back surface) facing a separator or a solid electrolyte membrane.
[0079] The above Index 1 and Index 2 can be verified by visualizing the distribution of electrode materials, particularly conductive materials, over an arbitrary cross-section of the electrode active material layer, and by calculating the perimeter and area of the portion where the conductive material is distributed (conductive material region) and substituting them into the above values. The verification of the distribution of electrode materials included in the electrode active material layer is for microscopic dimensions below the micro scale. Accordingly, the visualization of the conductive material distribution can be verified by analyzing the conductive network of the cross-section of the electrode active material layer through electronic visualization methods such as atomic force microscopy and scanning diffusion resistivity microscopy, as described below.
[0080] Next, the method for calculating the above Index 1 and Index 2 will be explained in detail.
[0081] The above method comprises the step (step 1) of obtaining an electrode cross-section sample by exposing an arbitrary cross-section inside an electrode for an electrochemical device;
[0082] Step 2: Acquiring resistance value data of the electrode active material and conductive material of the electrode cross-section sample using a scanning diffusion resistance microscope;
[0083] It includes the step of obtaining a log-scale image and histogram of the resistance value data (step 3); and the step of calculating exponent 1 and / or exponent 2 (step 4). Each step is described in more detail as follows.
[0084] (Step 1)
[0085] First, a dry electrode is prepared, and an electrode cross-section sample is manufactured by exposing an arbitrary cross-section within the electrode active material layer. The electrode may include an electrode active material layer formed on at least one surface of a current collector, and the electrode active material layer comprises an electrode active material, a conductive material, and a binder resin. Next, the surface of the electrode active material layer is removed to a predetermined thickness using an ion beam of ion milling to expose a cross-section within the electrode active material layer. Ion milling refers to a method of etching a material by accelerating ions of an inert gas from a broad beam ion source to a sample surface in a vacuum state. Ion milling is based on the sputtering phenomenon, in which ions or atoms of an inert gas (Argon) are accelerated to an appropriate voltage to cause atoms on the sample surface to detach. Through this, an electrode cross-section sample having a clean cross-section without physical damage can be manufactured, and the conductive material region in the electrode can be identified more clearly. According to one embodiment of the present invention, the inert gas may be argon. In this way, by irradiating the electrode for the secondary battery with an argon ion beam, the electrode cross-section sample can be manufactured more stably. In one embodiment of the present invention, the ion beam current of the ion milling device may be 100 μA or more and 250 μA or less. Specifically, the ion beam current of the ion milling device may be 110 μA or more and 150 μA or less, or 200 μA or more and 230 μA or less. By adjusting the ion beam current of the ion milling device to the aforementioned range, the manufacturing time of the electrode cross-section sample can be shortened, and the phenomenon of electrode materials being redeposited on the cross-section of the sample can be prevented, thereby enabling the production of an electrode cross-section sample having a cleaner cross-section.
[0086] By utilizing this ion milling, electrode surface information with very good roughness can be obtained, and desired information, such as observation through an electron microscope or visualization data, can be acquired.
[0087] FIGS. 11a and FIGS. 11b schematically illustrate a method for preparing an electrode cross-section sample. Referring to the above, the cross-section sample is prepared by etching and removing a portion (11s) from the surface to a predetermined depth with respect to the thickness direction (height) of the electrode active material layer using ion milling, thereby exposing a predetermined plane inside the electrode active material layer.
[0088] Meanwhile, in one embodiment of the present invention, the step of preparing the electrode cross-sectional sample may further include the step of impregnating the electrode with a polymer containing epoxy groups before applying the ion milling, thereby filling the internal pores of the electrode for a secondary battery with the polymer containing epoxy groups. The method of impregnating the electrode with a polymer containing epoxy groups may be carried out by a method conventional in the art. For example, methods such as applying the polymer containing epoxy groups onto the electrode or immersing the electrode in a polymer solution containing epoxy groups may be applied.
[0089] According to one embodiment of the present invention, the method for analyzing the electrode for a battery may further include the step of measuring the resistance value of the polymer containing epoxy groups filled in the pores of the electrode cross-section sample. By filling the internal pores of the electrode for a secondary battery with a polymer containing epoxy groups, the resistance value of the pores within the electrode cross-section sample can be obtained using a scanning diffusion resistance microscope. Specifically, resistance value data can be obtained by measuring the resistance value of the polymer material filling the pores. Through this, the region where the pores are located can be identified, and the electrode active material region, the conductive material region, and the pore region of the electrode cross-section sample can be distinguished more accurately from the composite image.
[0090] According to one embodiment of the present invention, the polymer containing the epoxy group may be an epoxy resin polymer containing a cyclic structure within its molecular structure, and specifically, an epoxy resin polymer containing an aromatic group (e.g., a phenyl group) may be used. Specific examples of the epoxy group-containing polymer containing the aromatic group may be one or more of the following: a biphenyl-type epoxy group-containing polymer, a dicyclopentadiene-type epoxy group-containing polymer, a naphthalene-type epoxy group-containing polymer, a dicyclopentadiene-modified phenol-type epoxy group-containing polymer, a cresol-based epoxy group-containing polymer, a bisphenol-based epoxy group-containing polymer, a xylock-based epoxy group-containing polymer, a polyfunctional epoxy group-containing polymer, a phenol novolak epoxy group-containing polymer, a triphenolmethane-type epoxy group-containing polymer, and an alkyl-modified triphenolmethane epoxy group-containing polymer, but are not limited thereto. Specific examples may include, but are not limited to, any one of epoxyethane (ethylene oxide), 1,3-epoxypropane (trimethylene oxide), and bisphenol-A-epichlorohydrin.
[0091] (Step 2)
[0092] Next, when the electrode cross-section sample is prepared in step 1 above, a 2D scale map of the resistance distribution of the sample cross-section is obtained using a conductivity network analysis method (Scanning Spreading Resistance Microscopy). Figure 1 is an exemplary 2D scale map image of Example 1 obtained by the above method.
[0093] Specifically, an image converted to a 2D scale can be obtained by scanning the surface of the cross-sectional sample using an Atomic Force Microscopy (AFM) device. Through this measurement, a map is obtained in which the height of the electrical resistance value appears as shades of color, and the distribution of surface resistance can be visually confirmed based on the difference in hue (shade). First, a sample for measurement is prepared using an Atomic Force Microscopy (AFM) device. The cross-sectional sample prepared by the above process is attached to a metal disc for the AFM with the cross-section facing upward, and silver paste or the like is applied to form a conductive path between the part other than the milled cross-section and the metal disc for the AFM. The AFM measurement sample prepared in this way is loaded into the device, and after laser alignment, the cross-section is selected as the measurement area using an optical microscope. Subsequently, an atomic force microscope probe is brought into contact with the electrode cross-section, and the current flowing through the sample between the atomic force microscope probe and the contact electrode is measured to obtain the diffusion resistance from the measured current. According to one embodiment of the present invention, the operating conditions of the scanning diffusion resistance microscope for analyzing the electrode cross-sectional sample are, for example, as follows. The above-mentioned AFM equipment is not limited to any specific type as long as it is capable of visualizing the resistance distribution according to the scanning diffusion resistivity microscopy method of the present invention. For example, one from Cypher ES (Oxford Instruments) may be used. According to a specific example of the present invention, Dual-gain ORCA may be used as the cantilever holder, and AR (Oxford Instruments) may be used as the driving software. As specific driving conditions, a Contact Mode may be set, the acquired image pixels may be set to 512x512 to 1024x1024, the scan rate may be set to 0.2 Hz or higher and 1.0 Hz or lower, and the bias may be 2.It can be set to 0 V or less, and the set point can be set to 1.0 V or less. For example, the image pixels can be set to 512x512, the scan rate to 0.5 Hz, the bias to 2.0 V or less, and the set point to 0.2 V. As for the AFM probe, a solid diamond AFM probe made of boron-doped single crystal diamond (AD-40-As, Adama) can be used.
[0094] Meanwhile, in one embodiment of the present invention, it is preferable to measure the obtained cross-sectional sample using AFM under conditions of non-exposure to the atmosphere, such as in a glove box. At this time, the cross-sectional sample can be loaded into a sealed cell body to maintain a non-exposure to the atmosphere.
[0095] (Step 3)
[0096] Once a 2D scale map is obtained through Step 2 above, the conductive material region is defined. Since the term 'definition' is applied using a visual display method, it may be described as 'masking'. For example, FIGS. 17 and 18 show the conductive material region identified from the histogram for the electrode of Example 7, indicated in black.
[0097] The method for defining the above-mentioned conductive material region can be specifically described as follows.
[0098] First, resistance value data obtained using a scanning diffusion resistance microscope is processed and converted to a log scale to obtain a log scale image (log(resistance) image), and a [log resistance distribution histogram] is extracted from the log scale image, in which the materials constituting the electrode cross-section sample are distinguished and displayed.
[0099] It is possible to determine whether the region corresponding to each pixel on the above histogram is an electrode active material region, a pore or binder region, or a conductive material region, and to quantify the distribution of the conductive material region in the above 2D mapping image using the information of each pixel for which the region has been determined.
[0100] Specifically, the log(R / Ω) value corresponding to the minimum value between the conductive material peak and the electrode active material peak in the above histogram is set as a threshold, and the region having a value smaller than that value is masked as the conductive material region. At this time, the numerical value can be corrected by adding or subtracting 0.1 to 0.5 from the above minimum value.
[0101] In one embodiment, the correction may be to add a value of 0.1 to 0.5 to the log(R / Ω) value corresponding to the minimum value. This is intended to correct the portion that is not indicated as a conductive material region because the active material region and the conductive material region overlap in the histogram. For example, the correction value may distinguish the left and right sides centered on the conductive material region peak of the histogram, and correct the low point of the right side to have a value equal to the horizontal distance from the peak to the low point on the left.
[0102] FIGS. 5, FIGS. 6, and FIGS. 12a each show a [log resistance distribution histogram] extracted based on a log scale image (log(resistance) image) for the electrodes of Example 1, Comparative Example 1, and Example 7. By referring to this, the conductive material peak and the electrode active material peak can be identified, and the minimum value between them can be determined. However, as previously explained, since there is a conductive material region that is not displayed because it overlaps with the active material region even in the section after the minimum value, the values are corrected as described above. FIG. 12b is an example diagram showing the expected shape of the overlapping active material region and the conductive material region in the histogram before correction for the electrode of Example 7.
[0103] When correction is made in this way, parts that overlap with the active material region and are not identified on the histogram can be incorporated into the conductive material region, allowing for a more accurate evaluation of values.
[0104] Meanwhile, FIG. 17 shows the conductive material region masked in the SSRM image based on the values before correction. The conductive material region is masked using a color that is not present in the original image, and in the present embodiment, it is masked in black. If you examine the circled area indicated by the dotted line in FIG. 17, you can see that there is a part of the conductive material that remains unmasked. In the unmasked part, if the color is checked, it is confirmed that the part remains blue. Meanwhile, FIG. 18 shows the conductive material region masked based on the values after correction, and it can be seen that the part that was not masked in FIG. 17 (the part that remained blue) is masked in black in FIG. 18.
[0105] Meanwhile, among the areas masked by the conductive material, the areas located within the active material are deleted to eliminate errors. This is because the errors are errors that occurred during the sample manufacturing process, such as conductive material adhering to the exposed cross-section of the active material during the cross-sectional sample preparation process, or errors that occurred during imaging processing, and it is evident that the conductive material is not distributed within the active material of the actual electrode, so it is desirable to remove them.
[0106] Meanwhile, after the conductive material region is masked, an image showing only the conductive material region is extracted (contrast masking) as shown in FIG. 2, FIG. 4, FIG. 6, the bottom of FIG. 13, the bottom of FIG. 14, and FIG. 16, and is provided for the calculation in Step 4.
[0107] In one embodiment of the present invention, the masking of the conductive material region can be performed using a program that visualizes and processes data obtained through scanning probe microscopy, such as AFM. In one embodiment of the present invention, Gwyddion software can be used for the masking. Meanwhile, if there are many images with excessively small pixel sizes among the images, it is difficult to accurately determine the perimeter or area of the conductive material region, and errors may occur as they act as noise when calculating the dispersion. Accordingly, images with excessively small pixels can be removed during the masking process. For example, when using the Gwyddion program, small areas of less than 3 pixels can be deleted using a grain-filtering function so that they are not masked as the conductive material region. If fine areas of less than 3 pixels are included, the perimeter of the conductive material region may be calculated as an excessively high value, so they are removed for measurement. Meanwhile, FIG. 5 shows a histogram obtained by the above method, which confirms that the active material region and the conductive material region are distinguished.
[0108] (Step 4)
[0109] Once the masking of the conductive material region is completed through the above (step 3) (i.e., the conductive material region is determined), the perimeter and area of the masked region are checked, and through this, Index 1 according to the above [Equation 1] can be calculated. In the above [Equation 1] Boundary measured applies the perimeter value of the masking area, and A applies the area value of the masking area.
[0110] In addition, the radius of a circle having an area equal to the area of the masking region can be calculated, and the circumference of the circle can be calculated from this. Index 2 according to [Equation 2] can be calculated by substituting the circumference of the circle into A.
[0111] Meanwhile, in the present invention, the area and perimeter of the masked conductive material region can be calculated using an image processing program such as Gwyddion software. FIG. 19 shows a display screen showing the area and perimeter calculated through the program.
[0112] dry electrode manufacturing method
[0113] In one embodiment of the present invention, a dry electrode satisfying indices 1 and 2 can be obtained by the following manufacturing method.
[0114] For example, the above dry electrode manufacturing method is,
[0115] (S10) A step of preparing a powder blend comprising an electrode active material, a conductive material, and a binder resin;
[0116] (S20) A step of kneading the powdered blend at a temperature range of 70℃ to 200℃ to produce a mixture mass;
[0117] (S30) A step of crushing the above mixture lumps to obtain a mixed powder containing mixed particles; and
[0118] (S40) A step of calendering the electrode powder to obtain a free-standing type dry electrode film; is included.
[0119] In addition, the electrode dry electrode film obtained in (S40) can be bonded to one or both sides of an electrode current collector to be manufactured into a dry electrode (S50).
[0120] Preparation of mixed powder
[0121] First, a mixed powder for dry electrodes is prepared.
[0122] The above-mentioned electrode mixed powder is a powdered electrode material comprising an electrode active material and a binder polymer, and may be obtained by crushing a mass of a mixture comprising an electrode active material and a binder polymer, for example, as described below. In this specification, the above-mentioned mixed powder refers to an assembly of mixed particles comprising two or more electrode materials. The individual mixed particles constituting the above-mentioned mixed powder may include one or more selected from an electrode active material, a binder, and a conductive material. In a specific embodiment, the above-mentioned mixed particles may include an electrode active material and a binder. Additionally, the particles may further include a conductive material. Meanwhile, the above-mentioned electrode powder may include one or more of the electrode active material, binder, and conductive material that remain and do not form the above-mentioned mixed particles.
[0123] Meanwhile, the above-mentioned electrode mixture powder can be obtained by the following manufacturing method.
[0124] Dry blending
[0125] First, an electrode material mixture comprising an electrode active material and a binder polymer is prepared. The electrode material mixture may further include the aforementioned conductive material and / or additives as needed, and the content ratios shall be in accordance with the aforementioned details. The mixing for preparing the mixture is performed so that the electrode materials, such as the electrode active material and the binder polymer, can have a uniformly dispersed phase within the mixture. Since the present invention is manufactured as a dry electrode that does not use a solvent, the mixing is performed in a powder form without the introduction of a solvent. Therefore, the mixing can be performed by various methods, not limited to any method, as long as it enables simple mixing of the electrode materials. For example, it can be performed by methods such as introducing the electrode materials into a known device like a mixer or blender and stirring them.
[0126] In a specific embodiment, the electrode materials can be mixed by introducing them into a device such as a mixer or blender in powder form.
[0127] In one embodiment of the present invention, the mixing time is not particularly limited but can be performed for 1 second to 10 minutes. Meanwhile, the mixing speed is not particularly limited but can be appropriately controlled within a range of about 3,000 rpm to 30,000 rpm. As a specific example, in terms of ensuring high uniformity, the mixing can be prepared by mixing in a mixer at 5,000 rpm to 20,000 rpm for 30 seconds to 2 minutes, and more specifically at 10,000 rpm to 15,000 rpm for 30 seconds to 1 minute.
[0128] As will be described later, the binder resin is mainly fiberized through step (S20). However, some thick fiberization may also proceed in step (S10).
[0129] Binder fiberization process
[0130] Next, a fiberization process is performed on the electrode material mixture obtained above to fiberize the binder polymer. In the present invention, the fiberization process may preferably be performed using a low-shear kneading method, and may be carried out, for example, through a dough mixer such as a kneader. Through this kneading, the binder polymer is fiberized, and electrode materials, such as the electrode active material introduced in powder form, are combined or connected to form a lump of mixture. Since the kneading does not involve the addition of a solvent, the lump of mixture may have a solid content of 100%. Through this kneading, the binder resin is fiberized, and the electrode active material and conductive material are combined or connected to obtain a lump-shaped mixture.
[0131] In one embodiment of the present invention, the mixing may be controlled at a speed of 10 rpm to 100 rpm. For example, the mixing may be controlled at 20 rpm or more or 40 rpm or more within the above range, and the upper limit may be controlled at a speed of, for example, 70 rpm or less. The mixing may be performed for 1 minute to 10 minutes. For example, it may be performed for 3 minutes to 7 minutes at a speed of 40 rpm to 70 rpm within the above range.
[0132] More preferably, the above kneading can be performed within 5 minutes or within 3 minutes. The lower the tap compression ratio in the obtained electrode mixture powder, the better the processability of manufacturing an electrode film using the powder is; the tap compression ratio decreases during the initial stages of kneading and then shows almost no change after a certain point. Since excessive kneading time leads to excessive fiberization and causes the fiberized binder resin filaments to break, it is sufficient to secure an appropriate tap compression ratio by controlling the kneading time within the above range.
[0133] Meanwhile, the above mixing can be controlled in a range of 10 / s to 500 / s. In a specific embodiment of the present invention, the mixing can be performed for 1 minute to 30 minutes, and the shear rate can be controlled in a range of 30 / s to 100 / s.
[0134] In addition, this mixing step can be performed under high temperature and pressure conditions above atmospheric pressure, and more specifically, under pressure conditions higher than atmospheric pressure. More specifically, the mixing can be performed in a range of 20°C to 230°C, and within this range, it can be controlled to a range of 20°C or higher, 50°C or higher, and the upper limit can be controlled to a range of 230°C or lower, or 200°C or lower.
[0135] If the mixing is performed at a low temperature outside the above range, the fiberization of the binder polymer and the aggregation of the input materials do not occur well, so film formation may not be easily achieved during the subsequent calendering process to form a sheet-shaped electrode film. On the other hand, if the mixing is performed at too high a temperature, the fiberization of the binder polymer occurs rapidly, and the fibers that have already been formed may be cut by the shear force continuously applied during the mixing process, which is undesirable.
[0136] In addition, it can be performed at a pressure above atmospheric pressure, specifically at a pressure of 1 atm to 3 atm, and more specifically at 1.1 atm to 3 atm. If performed outside the above range at a pressure too high, it is undesirable because excessive shear force and pressure may be applied, which may cause the formed fibers to be cut or the density of the mixture lumps to become too high. That is, according to the present invention, the intended effect of the present invention can be achieved when a low-shear mixing process is performed under high temperature and pressure above atmospheric pressure conditions instead of high-shear mixing.
[0137] Grinding
[0138] Next, the mixture mass prepared through the above mixing step is crushed to obtain a powdered mixed material for electrodes.
[0139] Although the mixture mass obtained through the above mixing process may be immediately pressurized to form a sheet (calendering process), in this case, strong pressure and high temperature must be applied to form it to the target thickness; consequently, problems may arise where the density of the dry electrode film becomes too high or a uniform film cannot be obtained. Therefore, the mixture mass obtained as described above is crushed to produce a mixed powder for electrodes.
[0140] At this time, the grinding may be performed using a device such as a blender or a grinder, although it is not limited to this. In one embodiment of the present invention, the grinding may specifically be performed in a grinder at a speed of 5,000 rpm to 20,000 rpm, or 10,000 rpm to 18,000 rpm. Meanwhile, the grinding process may be performed for 30 seconds to 10 minutes, specifically for 30 seconds to 1 minute. If the grinding is performed outside the above range at too low an rpm or for too short a time, it may not be sufficiently ground, resulting in powder particles of an unsuitable size for film formation; conversely, if it is performed at too high an rpm or for too long, a large amount of fine powder may be generated, which is undesirable.
[0141] In one embodiment of the present invention, the particle size (D50) of the mixed particle obtained through the grinding process can be appropriately controlled within the range of 10 μm to 800 μm. In a specific embodiment, the particle size (D50) of the mixed particle can be controlled within the range of 100 μm to 800 μm.
[0142] Meanwhile, in the present invention, the electrode mixture obtained above comprises PTFE and / or polyolefin as a binder resin, and the degree of crystallization (Xc) of the binder resin may be 20% or less.
[0143] In the present invention, the degree of crystallization (Xc) can be measured using differential scanning calorimetry (DSC) and is based on the temperature (peak temperature) at the point where the highest enthalpy is observed during crystallization. Specifically, the degree of crystallization is the melting enthalpy (△Hm) value measured by DSC relative to the melting enthalpy (△Hm) of a theoretically perfect crystal (degree of crystallization 100%). 0It is expressed as a percentage by dividing by the value of )(equilibrium heat of fusion), and can be calculated by [Equation 3] below. Here, the theoretical enthalpy of melting of a perfect crystal (△Hm 0 The value can be referenced in the Polymer Handbook (J. Brandrup et al., 2003) or academic papers such as *Polymer*. For example, the theoretical melting enthalpy value of perfect crystal PTFE is 85.4 J / g (*Polymer* Vol. 46 (2005) 8872–8882). Meanwhile, thermal analysis of polymers, such as DSC, can typically be measured and calculated according to ASTM D3418-21.
[0144] [Equation 3]
[0145] Xc(%) = (△Hm ÷ △Hm 0 ) × 100
[0146] Meanwhile, in one embodiment of the present invention, the electrode mixture powder having a low resistivity value is advantageous in terms of minimizing the generation of fine powder and improving the processability of forming the powder into a film. In one embodiment of the present invention, it is preferable that the resistivity of the mixture powder is 700 Ω·cm or less when pressurized at a pressure of 50 MPa. If the resistivity is high outside the above range, the resistance of the composite film and dry electrode subsequently manufactured increases, which may degrade battery performance, so it is not desirable.
[0147] The above resistivity can be calculated by placing 2g of electrode powder into a ceramic container with a diameter of 22mm that has 4 point probes embedded in the bottom, applying a force of 2000kgf, i.e., a pressure of approximately 50MPa, measuring the resistance, and multiplying it by the thickness of the electrode powder.
[0148] Dry electrode film and dry electrode
[0149] Furthermore, the present invention relates to a dry electrode film comprising the above-mentioned mixed powder and a dry electrode comprising the above-mentioned dry electrode film. The above-mentioned dry electrode film refers to a free-standing type single sheet manufactured using an electrode material comprising an electrode active material and a binder without the involvement of a solvent. In this specification, the term "free-standing type" means that it can maintain a shape independently without relying on other components and can be moved or handled on its own. In the present invention, the above-mentioned dry electrode film may be formed by compressing the electrode mixed powder as described below. For example, the electrode mixed powder may have a shape forming a layered structure by being accumulated by compression. In the present invention, the dry electrode comprises an electrode active material layer derived from the free-standing dry electrode film. For example, the dry electrode may have a current collector and an electrode active material layer derived from the dry electrode film disposed on at least one side of the current collector, and the dry electrode film and the current collector may be formed by bonding through a lamination process or the like.
[0150] Next, the method for manufacturing the dry electrode film and the dry electrode is described in detail.
[0151] dry electrode film manufacturing method
[0152] In one embodiment of the present invention, a dry electrode film may be obtained by a method of compression molding the electrode mixture powder. In this specification, the process of manufacturing a sheet-shaped dry electrode film by compressing the electrode mixture powder is described as a calendering process. By the calendering process, the dry electrode film may be prepared in the form of a sheet having a predetermined thickness. For example, the dry electrode film may have the form of a strip with an aspect ratio greater than 1. In one embodiment of the present invention, the dry electrode film may have a thickness of 50 μm to 300 μm.
[0153] For example, the calendering process may be performed by a calendering method in which the mixed powder for the electrode is supplied to a calender device and heat-pressed using roll press(s) included in the calender device. Additionally, the calendering process may be performed by a roll-to-roll continuous process.
[0154] In one embodiment of the present invention, the calender device may include a roll press section in which two rollers are arranged to face each other, and a mixed powder for electrodes may pass through the roll press section and be compressed into a sheet shape. The roll press section may be arranged in a plurality of continuous numbers so that the compression of the dry electrode film may be performed multiple times. The number of roll press sections may be appropriately adjusted considering the thickness or rolling rate of the dry electrode film. FIG. 9 schematically illustrates the calendering process (100). Referring to FIG. 9, the mixed powder (120) is pressed multiple times by a calender device including a plurality of calendering rollers (110) to manufacture a dry electrode film (130).
[0155] Meanwhile, each of the above-mentioned roll press sections can independently control the rotational speed ratio of the two rollers within a range of 1:1 to 1:10. For example, in one or more roll press sections, the rotational speed ratio of the two rollers is controlled to a ratio of 1:1 to 1:3. Additionally, the temperature of the rollers of each roll press section can be independently controlled within a range of 100°C to 250°C. A dry electrode film can be manufactured by such a calendering process. In one embodiment of the present invention, the crystallization degree (d) of the binder resin in the obtained dry electrode film can be controlled to be 10% or less. If the crystallization degree of the obtained dry electrode film exceeds 10%, the crystallization degree can be controlled by adjusting the gap between the two rollers of the roll press section or by controlling the speed ratio. For example, the degree of fiberization of the binder can be increased by reducing the gap and / or increasing the speed ratio. In this way, when the degree of crystallinity is controlled to 10% or less, the flexibility of the dry electrode film increases, which has the advantage of preventing breakage or cracking when wound for storage or unwound. In addition, mechanical strength can be improved, such as tensile strength and tensile elongation, as flexibility increases.
[0156] Meanwhile, in the present invention, the dry electrode film may have a porosity of 20 vol% to 50 vol%, and within the above range, preferably, it may be controlled to a value of 40 vol% or less or 35 vol% or less. When the porosity satisfies the above range, it is desirable in terms of various effects. On the other hand, if it falls outside the above range and the porosity is too small, it is difficult to impregnate the electrolyte, which is undesirable in terms of lifespan characteristics, output characteristics, etc., and if it is too large, the volume required to achieve the same capacity increases, which is undesirable in terms of energy density relative to volume. In one embodiment of the present invention, the porosity can be obtained by [Equation 4] as follows, by measuring the apparent density of the dry electrode film and using the actual density calculated based on the actual density and composition of each constituent component.
[0157] [Equation 4]
[0158] Porosity (vol%) = { 1 - (Apparent Density / Actual Density)} x 100
[0159] dry electrode manufacturing method
[0160] Next, a method for manufacturing a dry electrode according to one embodiment of the present invention will be described. In one embodiment of the present invention, the dry electrode may be manufactured by bonding a dry electrode film and a current collector through a lamination process. Specifically, the dry electrode film obtained above is laminated on one or both sides of a current collector, and the current collector and the dry electrode film are bonded through a lamination process to manufacture the electrode. The lamination may be a step of rolling and attaching the dry electrode film onto the current collector. The lamination may be performed by a roll press method using a lamination roller, wherein the lamination roller may be controlled to a temperature of 20°C to 200°C. FIG. 10 schematically illustrates a lamination process according to one embodiment of the present invention. Referring to this, a dry electrode film (230) is bonded to a current collector (230) to manufacture a dry electrode (240), and the lamination process is performed by applying pressure by a lamination roller (210). Meanwhile, in the present invention, the dry electrode film attached to the current collector as a result of lamination may be referred to as the electrode active material layer. Furthermore, in the present invention, the dry electrode film and the electrode active material layer are derived from the electrode mixed powder, and the content ratio of the materials in the dry electrode film and the electrode active material layer may have the same range as that of the mixed powder.
[0161] QBR
[0162] Meanwhile, in one embodiment of the present invention, the binder polymer includes a fluorine-containing binder, and the electrode active material layer may have a QBR (Quantified Binder Ratio) of 1.1 or less.
[0163] The above QBR is defined by the following [Equation 5].
[0164] [Equation 5]
[0165] QBR = Bs / Bf
[0166] In the above [Equation 5], Bs represents the average value of the fluorine content in the surface region of the electrode active material layer from the outermost surface of the electrode active material layer up to within 15% of the total thickness of the electrode active material layer, and Bf represents the average value of the fluorine content in the bottom region of the electrode active material layer from the interface of the electrode active material layer facing the current collector up to within 15% of the total thickness of the electrode active material layer. FIG. 7 is a schematic diagram of an electrode according to one embodiment of the present invention. Referring to FIG. 7, the electrode (10) comprises an electrode current collector (12); and an electrode active material layer (11) located on the electrode current collector (12) and comprising an electrode active material and a binder polymer. The electrode active material layer (11) has, based on the total thickness (d), an electrode active material layer surface region (11s) extending from the outermost surface of the electrode active material layer to within 15% of the total thickness (d) of the electrode active material layer, and an electrode active material layer bottom region (11f) extending from the electrode active material layer interface facing the current collector to within 15% of the total thickness (d) of the electrode active material layer. In the above mathematical formula QBR, Bs represents the average value of the fluorine content in the electrode active material layer surface region (11s), and Bf represents the average value of the fluorine content in the electrode active material layer bottom region (11f). At this time, QBR can be calculated by the following method.
[0167] First, an electrode to be tested for QBR is selected, and a cross-section of the selected electrode is fabricated using argon ion milling. Subsequently, the components within the electrode active material layer of the fabricated electrode cross-section are mapped using an Energy Dispersive X-ray Spectroscopy (EDS) detector of a Scanning Electron Microscope (SEM).
[0168] A line profile is extracted in the direction of the electrode active material layer thickness from the EDS mapping results, and among the extracted line profile results, the average value (Bs) of the fluorine content of the fluorine-containing binder in the surface region of the electrode active material layer and the average value (Bf) of the fluorine content of the fluorine-containing binder in the bottom region of the electrode active material layer are extracted, and the QBR value is calculated using [Equation 5] above.
[0169] At this time, the surface region of the electrode active material layer is a region from the outermost surface in the thickness direction of the electrode active material layer to within 15% of the total thickness of the electrode active material layer, and the bottom region of the electrode active material layer is a region from the interface of the electrode active material layer facing the current collector to within 15% of the total thickness of the electrode active material layer.
[0170] Figure 8 is a schematic diagram for calculating the QBR value of the electrode active material layer. Referring to Figure 8, the X-axis represents the thickness of the electrode active material layer, i.e., the distance from the surface to the current collector, and the Y-axis represents the fluorine component intensity. Line A represents the intensity of the fluorine component of the fluorine-containing binder extracted by EDS mapping the fluorine component within the electrode active material layer of the electrode cross-section, and Line B is a trend line representing the trend of Line A, which is a line obtained by smoothing using the LOWESS smoothing method, i.e., the Locally-Weighted Scatterplot Smoother.
[0171] The above QBR value is a numerical value representing the uniformity of the fluorine-containing binder's distribution in the thickness direction within the electrode active material layer, based on the ratio of the fluorine-containing binder content in the surface region to the fluorine-containing binder content in the bottom region of the electrode active material layer. In this case, the content of the fluorine-containing binder can be inferred from the fluorine component contained in the fluorine-containing binder used.
[0172] The above QBR value is 1.1 or less, and according to one embodiment of the present invention, the above QBR value may be 0.95 or more, 0.97 or more, 1.03 or less, 1.05 or less, and may also be 0.95 to 1.05. When the above QBR value satisfies the range of 1.1 or less, the problem of the fluorine-containing binder migrating to the electrode surface and the fluorine-containing binder content in the surface region becoming higher than the fluorine-containing binder content in the bottom region of the electrode active material layer does not occur, and as a result, the distribution of the binder in the thickness direction of the electrode active material layer becomes even, so that the binder content in the part close to the current collector does not decrease, thereby improving the adhesion between the current collector and the electrode active material layer, and the conductivity on the surface of the electrode active material layer and the resulting charge / discharge speed can also be improved. Specifically, the above fluorine-containing binder is polytetrafluoroethylene (PTFE); It may include PVdF-based copolymers such as PVdF (polyvinylidene fluoride) and PVdF-HFP (polyvinylidene fluoride-co-hexafluoropropylene), or two or more of these. Additionally, the fluorine-containing binder may include polytetrafluoroethylene alone, or additionally include one or more PVdF-based copolymers such as PVdF (polyvinylidene fluoride) and PVdF-HFP (polyvinylidene fluoride-co-hexafluoropropylene) in addition to polytetrafluoroethylene.
[0173] Compression ratio
[0174] Meanwhile, according to one embodiment of the present invention, the dry electrode film may have a compression ratio of 30 to 50%, or 35 to 50%, or 40 to 50%. The compression ratio may be defined as the ratio of the thickness at which the dry electrode film is compressed at the moment of lamination to combine the dry electrode film with a current collector, and can be expressed by the following [Equation 6].
[0175] [Equation 6]
[0176] Compression ratio (%) = Tp / T1 × 100
[0177] In [Equation 6],
[0178] Tp represents the thickness of the dry electrode film compressed by pressure during the lamination step, and T1 represents the thickness of the dry electrode film before the lamination step.
[0179] In the present invention, by adjusting the compression ratio to satisfy a specific range during the lamination step, it is possible to provide appropriate density and porosity of the dry electrode film and excellent bonding strength between the dry electrode film and the current collector.
[0180] When the above compression ratio satisfies the range of 30% to 50%, the pressure applied to the dry electrode film is sufficient to improve the adhesion between the dry electrode film and the current collector, and the problem of the electrode active material layer peeling off from the current collector in the electrode manufactured by the lamination process can be prevented, and the problem of the electrode active material layer showing a lower porosity than the target porosity or the current collector being damaged due to the density of the dry electrode film increasing more than necessary can be resolved.
[0181] In one embodiment of the present invention, when dry electrode films are laminated on both sides of the current collector, the compression ratio (%) of [Equation 6] may mean the following [Equation 7].
[0182] [Equation 7]
[0183] 30 ≤ (T1 + 0.5Tc - 0.5Tgap) / T1 × 100 ≤ 50
[0184] In [Equation 7], T1 represents the thickness of the dry electrode film before the lamination step, Tc represents the thickness of the current collector, and Tgap represents the gap between the first and second rolling rolls. Additionally, the rolling rate of the dry electrode film after the lamination step may be in the range of 20% or less, or 18% or less, or 15% or less, or 5% to 15%, or 6% to 15%, or 7% to 15%, or 9% to 13%. After the lamination step, the dry electrode film can be considered as an electrode active material layer. Here, the rolling rate can be defined as the ratio of the thickness of the dry electrode film after the lamination step to the thickness of the dry electrode film before the lamination step, and can be expressed by [Equation 8] below.
[0185] [Equation 8]
[0186] Rolling rate (%) = (T1-T2) / T1 × 100
[0187] In the above [Equation 8],
[0188] T1 refers to the thickness of the dry electrode film before the lamination step, and T2 refers to the thickness of the dry electrode film after the lamination step. When the above rolling rate satisfies the range described above, the electrode active material layer in the dry electrode after manufacturing can exhibit appropriate density and porosity, and the adhesion to the current collector can be improved.
[0189] In the above dry electrode film, the apparent density increase rate before and after lamination with the current collector can be expressed by the following [Equation 9]:
[0190] [Equation 9]
[0191] Apparent density growth rate (%) = (D2-D1) / D1×100
[0192] D1 is the apparent density (g / cm³) of the dry electrode film before the lamination step.3 Representing ),
[0193] D2 is the apparent density (g / cm³) of the dry electrode film (i.e., the electrode active material layer) after the lamination step. 3 It represents ).
[0194] The apparent density increase rate of the dry electrode film before and after lamination with the current collector may be 5% to 30%, or 7% to 25%, or 10% to 20%. At this time, D1 and D2 are 2.75 g / cm³ 3 Up to 3.5 g / cm³ 3 It may be within the range. Meanwhile, if the apparent density increase rate of the dry electrode film satisfies the above range, the adhesion between the dry electrode film and the current collector can be improved, and problems such as the porosity deviating from the target range or damage to the positive active material or current collector can be prevented.
[0195] The apparent density of the dry electrode film before and after lamination with the current collector can be calculated by measuring the weight and thickness of the dry electrode film before lamination, measuring the weight and thickness of the electrode after lamination, and determining the weight and thickness of the film after subtracting the weight and thickness of the current collector.
[0196] In one embodiment of the present invention, the active material loading amount of the dry electrode is 2.5 mAh / cm² 2 Up to 15mAh / cm 2 It could be, and specifically 4mAh / cm 2 Up to 10mAh / cm 2 It may be. Here, the loading amount of the active material is the value calculated by [Equation 10] below.
[0197] [Equation 10]
[0198] Loading amount of active material (mAh / cm²) 2 ) = Capacity of active material (mAh / g) x Weight content ratio of active material in dry electrode (wt%) x Weight per unit area of dry electrode (g / cm²) 2 )
[0199] In addition, in the above dry electrode, the interfacial resistance between the electrode active material layer and the current collector is 5 Ω·cm 2 Below, in detail, 2Ω·cm 2 It may be less than or equal to the above. Here, the interface resistance can be calculated by applying a current of 100 μA to the electrode using the MP (Multi Probe) resistance measurement method and measuring the resistance value between the electrode active material layer and the contactor using the potential difference measured between multiple probes. If the above range of interface resistance is satisfied, the battery performance of the secondary battery manufactured thereafter can be improved.
[0200] Furthermore, the present invention relates to an electrode assembly comprising a dry electrode obtained as described above and an electrochemical device comprising the same. The electrode assembly may include an anode, a cathode, and a separator interposed between the anode and the cathode. In another embodiment, the electrode assembly may include an anode, a cathode, and a solid electrolyte membrane interposed between the anode and the cathode. In each embodiment, the anode and / or cathode may be dry electrodes having the aforementioned characteristics.
[0201] The electrochemical device of the present invention includes all devices that perform electrochemical reactions, and specific examples include all types of primary and secondary batteries, fuel cells, solar cells, or capacitors such as supercapacitor devices. In particular, among the secondary batteries, a lithium secondary battery including a lithium metal secondary battery, a lithium-ion secondary battery, a lithium polymer secondary battery, or a lithium-ion polymer secondary battery is preferred.
[0202] Hereinafter, the present invention will be described in detail based on embodiments, comparative examples, and experimental examples according to the present invention so that those skilled in the art can easily understand it.
[0203] [Example]
[0204] Preparation of mixed powder for electrodes and dry electrode films
[0205] Examples 1 to 4 and Example 7
[0206] Lithium nickel cobalt manganese aluminum composite oxide (Li(Ni, Co, Mn, Al)O2), carbon black, and polytetrafluoroethylene (PTFE) were introduced into a blender and mixed at approximately 10,000 rpm for about 1 minute to prepare a mixture. Next, the temperature of the kneader was stabilized to approximately 150°C, and the mixture was placed into the kneader and kneaded under a pressure of approximately 1.1 atm to obtain a lump of the mixture. The kneading process was performed at a speed of approximately 50 rpm for about 5 minutes. The lump of the mixture was introduced into a blender, ground for approximately 40 seconds under conditions of approximately 10,000 rpm, and classified through a sieve with 1 mm pores to obtain a mixed powder for electrodes. Next, the mixed powder for electrodes was introduced into a first lap calender (roll diameter: 88 mm, roll temperature: approximately 100°C, approximately 20 rpm) and compressed to produce a dry electrode film. Next, the obtained dry electrode film was placed on both sides of an aluminum thin film (thickness 19 μm) and bonded by a lamination process maintained at approximately 150°C to obtain an electrode. In the obtained electrode, the thickness of the electrode active material layer on one side was approximately 80 μm. Meanwhile, the lithium nickel cobalt manganese aluminum composite oxide has a bimodal distribution and includes large particles (secondary particles) with a diameter of approximately 10 μm and single particles with a diameter of approximately 5 μm. Fig. 1 is an SSRM image of the electrode of Example 1, and Fig. 15 is an SSRM image of the electrode of Example 7. Meanwhile, Fig. 2 is an image of the electrode of Example 1, and Fig. 17 is an image confirmed by masking the conductive material region of the electrode of Example 7.
[0207] Examples 5 and 6
[0208] An electrode was obtained in the same manner as in Example 1, except that a monomodal distribution lithium nickel cobalt manganese aluminum composite oxide containing single particles with a diameter of about 5 μm was used. The top of Fig. 13 is an SSRM image of Example 5, and the bottom of Fig. 13 is an image confirmed by masking the conductive material area. The top of Fig. 14 is an SSRM image of Example 6, and the bottom of Fig. 14 is an image confirmed by masking the conductive material area.
[0209] The content ratios of the components used in Examples 1 to 6 above, the types of conductive materials, and the specific surface area of the conductive materials are summarized in Table 1 below.
[0210] division Example 1 Example 2 Example 3 Example 4 Example 7 Example 5 Example 6 Active material:conductive material:binder (weight ratio) 96.0:1.5:2.5 96.0:1.0:3.0 96.0:1.5:2.5 96.0:1.0:3.0 96.0:1.5:2.5 96.0:1.8:2.2 96.2:1.6:2.2 Types of conductive materials Carbon Black Carbon Black Carbon Black Carbon Black Carbon Black Carbon Black Carbon Black Specific surface area of conductive material (m²) 2 / g) 1400 1400 135 135 135 1400 1400
[0211] division Example 1 Example 2 Example 3 Example 4 Example 7 Example 5 Example 6 MP Resistance Active(Ω·cm) 15.3 41.4 57.6 78.4 55.4 6.55 19.83 MP resistance interface (Ω·cm) 2 ) 0.13 0.17 0.24 0.30 0.22 0.15 0.14
[0212] Comparative Examples 1 to 4
[0213] Lithium nickel cobalt manganese aluminum composite oxide (Li(Ni, Co, Mn, Al)O2), carbon black, and polytetrafluoroethylene (PTFE) were introduced into a blender and mixed at room temperature at approximately 10,000 rpm for about 1 minute to prepare a mixture. Next, the mixture was ground through a jet-milling process (feeding pressure 50 psi, grinding pressure 45 psi) to obtain a mixed powder for electrodes. In Comparative Examples 1 to 4, the kneading process performed in the example was not performed. The mixed powder for electrodes was introduced into a first lap calender (roll diameter: 88 mm, roll temperature: approximately 100°C, approximately 20 rpm) and compressed to produce a dry electrode film. Next, the obtained dry electrode film was placed on both sides of an aluminum thin film (thickness approximately 19 μm) and bonded by a lamination process maintained at approximately 150°C to obtain a dry electrode. The thickness of the electrode active material layer on one side of the obtained electrode was approximately 80 μm. Figure 3 is an image of the SSRM of Comparative Example 1, and Figure 4 is an image confirmed by masking the conductive material area. Meanwhile, the lithium nickel cobalt manganese aluminum composite oxide has a bimodal distribution and includes large particles (secondary particles) with a diameter of approximately 10 μm and single particles with a diameter of approximately 5 μm.
[0214] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Active material:conductive material:binder (weight ratio) 96.0:1.5:2.5 96.0:1.0:3.0 96.0:1.5:2.5 96.0:1.0:3.0 Types of conductive materials Carbon Black Carbon Black Carbon Black Carbon Black Specific surface area of conductive material (m²) 2 / g) 1400 1400 135 135
[0215] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 MP Resistance Active (Ω·cm) 96.3 124.5 118.0 153.8 MP resistance interface (Ω·cm) 2 ) 0.33 0.52 0.69 0.88
[0216] Preparation of cross-sectional samples
[0217] Electrodes obtained in Examples 1 to 7 and Comparative Examples 1 to 4 were prepared. A solution was prepared containing an epoxy-based polymer having a weight-average molecular weight of approximately 700 g / mol or less, which is a polymer containing epoxy groups. Each electrode was impregnated with the prepared epoxy-based polymer solution to fill the pores with the polymer. Subsequently, a focused argon (Ar) ion beam was irradiated onto the cathode for the secondary battery using an ion milling device (IB19520CCP, Jeol) to mill the surface, thereby producing a cross-sectional sample having a clean cross-section. During argon ion beam irradiation, the ion beam current was set to 170 μA, and the gas flow was 1.5 cm⁻¹. 3 / minutes, and was performed for 3 hours. The above cross-sectional sample exposed a cross-section parallel to the surface of the current collector at a depth of about 10% from the surface of the electrode active material layer downward.
[0218] SSRM analysis conditions
[0219] Equipment used: cypher ES (Oxford Instrument), Dual-gain ORCA cantilever holder
[0220] [Parameters]
[0221] Mode: contact
[0222] Sample / line: 512x512, Scan rate: 0.5Hz
[0223] Bias: ~2V, Deflection Setpoint Volts: ~0.2
[0224] Scan Angle: 90°
[0225] [AFM Mode]
[0226] Model: AD-40-As (Manufacturer: Adama)
[0227] Tip: Highly doped (B) single crystal diamond, tip height 300nm
[0228] Cantilever & bulk tip: diamond coated silicon, Reflex coating(Au)
[0229] F=180kHz, k=40N / m
[0230] Typical contact resistance: ~10kΩ
[0231] SSRM analysis method
[0232] After ion milling, the sample was transferred to a glove box under atmospheric non-exposure conditions and loaded onto an AFM puck. Subsequently, silver (Ag) paste was applied between the electrode portion and the AFM puck, excluding the fabricated cross-section, to form an additional conductive path. Next, the sample with the additional conductive path formed was loaded into a sealed cell body and mounted on an AFM instrument while maintaining an atmospheric non-exposure state. After laser alignment, the milled portion was selected as the measurement area using an optical microscope and measured under an Ar flow. In this manner, an SSRM image was obtained. Figures 1, 3, the top of Figure 13, the top of Figure 14, and Figure 15 are the SSRM images of Example 1, Comparative Example 1, Example 5, Example 6, and Example 7, respectively. The size of the observed image was set to 30 µm x 30 µm.
[0233] Masking of the challenge material area
[0234] The conductive material region was masked using Gwyddion software on the SSRM image obtained above.
[0235] First, a log(resistance) image was obtained, and a histogram of the log(resistance) distribution within the image was obtained. This was obtained using the Height distribution function in the Calculate 1D Statistical function provided by the software. A threshold was determined by applying a correction of 0.2 to the log(R / Ω) value corresponding to the lowest point between the peak corresponding to the conductive material and the peak corresponding to the electrode active material in the histogram. Figure 12a shows the histogram for Example 7, and according to this, log(R / Ω) = 7.2 was set as the threshold. Based on this, the conductive material region was masked. At this time, the area corresponding to pixels smaller than 3 pixels was deleted using the Grain filtering function, and the area located within the electrode active material was deleted. Meanwhile, referring to Figures 5, 6, and 12a, it was confirmed that pixels corresponding to the electrode active material and the conductive material were distinguished on the histogram obtained from the log-scale image. In other words, it was found that the distribution of the conductive material region could be easily quantified using the information of each pixel whose corresponding region was determined.
[0236] In addition, FIG. 2 shows the electrode of Example 1, the bottom of FIG. 13 shows the electrode of Example 5, the bottom of FIG. 14 shows the electrode of FIG. 6, FIG. 16 shows the electrode of Example 7, and FIG. 4 shows the electrode of Comparative Example 1, with the conductive material area masked and only the masked conductive material area displayed in shades of color.
[0237] Afterwards, the perimeter and area of the masked region were checked using the Grain-Summary function.
[0238] Next, exponents 1 and 2 were calculated by substituting the respective values into [Equation 1] and [Equation 2] above, and the results are shown in [Table 5] and [Table 6] below. As confirmed in Tables 5 and 6 below, the dry electrode of the example manufactured by applying the kneading process has an exponent 1 of 3.5 μm.-1 It showed values above, and exponent 2 showed a value of 10 or higher. However, the dry electrode prepared in the comparative example had an exponent 1 value of 3.5㎛. -1 It was less than, and the value of index 2 was found to be less than 10. As such, there were differences in the dispersion of the conductive material in the electrodes produced according to the electrode manufacturing process, and it was confirmed that the electrode according to the present invention had an excellent dispersion index.
[0239] Conductive material area (㎛) 2 )(Ratio to total area, %) Circumference of conductive material (㎛) Index 1 (㎛ -1 ) Index 2 Example 1 47.0(5.2%) 380.9 8.1 15.7 Example 2 75.5(8.3%) 381.1 5.05 12.37 Example 3 57.4(6.3%) 465.0 8.10 17.31 Example 4 42.7(4.7%) 379.1 8.88 16.37 Example 5 48.0(5.3%) 312.5 6.5 12.7 Example 6 34.2(3.8%) 10.1 16.7 19.83 Example 7 50.9(5.6%) 482.7 9.5 19.1
[0240] Conductive material area (㎛) 2 )(Ratio to total area, %) Circumference of conductive material (㎛) Index 1 (㎛ -1 ) Index 2 Comparative Example 1 125.6(13.9%) 342.6 2.73 8.62 Comparative Example 2 42.3(4.7%) 179.1 4.2 7.8 Comparative Example 3 152.0(16.8%) 428.4 2.8 9.8 Comparative Example 4 46.0(5.1%) 141.7 3.08 5.89
Claims
Claim 1 A dry electrode for an electrochemical device, wherein the dry electrode comprises an electrode active material layer derived from a dry electrode film, and the dry electrode active material layer comprises a mixed powder for electrodes, wherein the mixed powder for electrodes is heat-pressed to form a sheet shape having a predetermined thickness, and wherein the mixed powder for electrodes comprises an electrode active material and a binder polymer, and wherein the electrode active material layer has a conductivity dispersion index 1 (Index 1) according to [Equation 1] below for one or more arbitrary cross-sections within, which is 3.5 μm -1 A dry electrode wherein the conductivity dispersion index 2 (Index 2) according to [Equation 2] below is 10 or higher, the binder polymer comprises polytetrafluoroethylene (PTFE) and is fiberized by mechanical shear force, and the electrode active material layer comprises 80 wt% or more of the electrode active material relative to 100 wt% of the electrode active material layer: [Equation 1] Index 1 (㎛ -1 ) = Boundary measured / A[Equation 2]Index 2 = Boundary m easured / L circle In the above [Equation 1] Boundary measured represents the perimeter of the conductive material region measured at a predetermined cross-section of the electrode active material layer, and A represents the area of the portion defined as the conductive material region measured at a predetermined surface of the electrode active material layer, and in the above [Equation 2] L circle is the circumference of a circle having an area equal to the area of the measured conductive material region (2× )am. Claim 2 In claim 1, the electrode active material layer has a conductivity dispersion index 1 (Index 1) according to [Equation 1] for one or more arbitrary cross-sections inside, which is 3.5 μm -1 A dry electrode having the above, and having a conductivity dispersion index 2 (Index 2) according to [Equation 2] of 10 or more. Claim 3 A dry electrode according to claim 1 or 2, wherein the dispersion index 1 and dispersion index 2 are calculated by a method for evaluating the dispersion of a conductive material comprising: (Step 1) obtaining a cross-sectional sample in which an arbitrary cross-section inside the electrode active material layer is exposed; (Step 2) obtaining a 2D scale map of the resistance distribution of the cross-sectional sample; (Step 3) masking a conductive material region; and (Step 4) calculating the perimeter and area of the masked region, substituting them into Equation 1 and / or Equation 2, and confirming the dispersion of the conductive material in the electrode active material layer. Claim 4 A dry electrode according to claim 1, wherein the electrode active material layer is formed on one side of the electrode current collector, and the cross-section(s) are a plane parallel or perpendicular to the surface of the electrode active material layer facing the current collector. Claim 5 A dry electrode according to claim 1, wherein the binder polymer is the result of kneading. Claim 6 A dry electrode according to claim 1, wherein the binder polymer comprises a polyolefin. Claim 7 A method for manufacturing a dry electrode according to claim 1, wherein the method comprises the steps of mixing an electrode material including an electrode active material and a binder polymer (S10), kneading the mixed electrode material (S20), grinding the result of step (S20) to obtain an electrode composite powder (S30), and press-molding the electrode composite powder to manufacture a freestanding type dry electrode film (S40), wherein step (S20) is performed in a temperature range of 60°C or higher. Claim 8 In claim 7, the above (S20) is a method for manufacturing a dry electrode, wherein the method is performed in a temperature range of 60℃ to 250℃. Claim 9 A method for manufacturing a dry electrode according to claim 7, comprising the step of laminating the dry electrode film and the current collector by a lamination process. Claim 10 An electrochemical device comprising: an anode; a cathode; and a separator or solid electrolyte membrane interposed between the anode and the cathode; wherein at least one of the anode and the cathode is a dry electrode according to any one of claims 1, 2, 4, 5 and 6. Claim 11 (Step 1) obtaining a cross-sectional sample in which an arbitrary cross-section inside the electrode active material layer is exposed; (Step 2) obtaining a 2D scale map of the resistance distribution of the cross-sectional sample; and (Step 3) masking the conductive material region; and (Step 4) calculating the perimeter and area of the masked region, substituting them into the following Equation 1 and / or Equation 2, and confirming the dispersion of the conductive material in the electrode active material layer; wherein the dry electrode active material layer is derived from a dry electrode film and includes a mixed powder for electrodes, and the mixed powder for electrodes is heat-pressed to form a sheet shape having a predetermined thickness, and the mixed powder for electrodes includes an electrode active material and a binder polymer, and the electrode active material layer includes 80 wt% or more of the electrode active material relative to 100 wt% of the electrode active material layer, and in (Step 3), the conductive material dispersion index 1 (Index 1) according to [Equation 1] below is 3.5 μm -1 A method for measuring the conductivity dispersion of a dry electrode, wherein the conductivity dispersion index 2 (Index 2) according to the above and / or [Equation 2] below is 10 or greater: [Equation 1] Index 1 (㎛ -1 ) = Boundary measured / A[Equation 2]Index 2 = Boundary m easured / L circle In the above [Equation 1] Boundary measured represents the perimeter of the conductive material region measured at a predetermined cross-section of the electrode active material layer, and A represents the area of the portion defined as the conductive material region measured at a predetermined surface of the electrode active material layer, and in the above [Equation 2] L circle is the circumference of a circle having an area equal to the area of the measured conductive material region (2Х )am. Claim 12 An electrochemical device comprising: an anode; a cathode; and a separator or solid electrolyte membrane interposed between the anode and the cathode, wherein at least one of the anode and the cathode is a dry electrode according to the third.
Citation Information
Patent Citations
Dry particle based electro-chemical device and methodsof making same
KR101211968B1
Method for analysis of battery electrode
KR1020200044550A
Electrode for secondary battery
JP2007026984A
Electrode for secondary battery and secondary battery comprising the same
KR1020220014190A
A dry electrode comprising a mixure powder for an electrode
KR102650672B1
